1960
DOI: 10.1037/h0047488
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of the Pulfrich stereophenomenon as a function of target velocity.

Abstract: When filters of unequal optical density are placed in front of the two eyes, a target which is actually oscillating in a frontoparallel plane appears nearer than it really is for one direction of stroke and farther than it really is for the return stroke (Pulfrich stereophenomenon). Measurements of the near and far displace¬ ments of a black vertical rod have been obtained for a wide range of target velocities under each of several conditions of unequal binocular retinal illumi¬ nance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1960
1960
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 5 publications
4
13
0
Order By: Relevance
“…In good agreement with the theory of the Pulfrich effect, we found that smaller Pulfrich effects induced smaller car displacements [6,15,21,24] and that larger velocities were associated with larger car displacements [16]. We did not test the effect of a unilateral mydriasis on driving performance.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In good agreement with the theory of the Pulfrich effect, we found that smaller Pulfrich effects induced smaller car displacements [6,15,21,24] and that larger velocities were associated with larger car displacements [16]. We did not test the effect of a unilateral mydriasis on driving performance.…”
Section: Discussionsupporting
confidence: 69%
“…In such a situation, a moving object is perceived at an incorrect distance. Data from several psychophysical [3,6,12,15,16,21,34] and electrophysiological [4,32] investigations are consistent with the delay hypothesis. Other factors determining the magnitude of the stereophenomenon are pendulum velocity [16], level of illumination [15] and distance between observer and pendulum [17].…”
Section: Introductionsupporting
confidence: 80%
“…The data were interpreted as indicating that, where multiple cttes were available, sensitivity was the sum of the sensitivities to the component cues. The effect of target velocity on the magnitude of the Pulfrich phe nomenon has been investigated by Lit (111). The general finding is that over a large range of velocities the general view of the Pulfrich phe nomenon (as the production of an apparent disparity due to variations in the latent period with different stimulus intensities) seems to hold.…”
Section: Some Additional Psychophysical Relationsmentioning
confidence: 95%
“…Geometrically, beside being seen from different angles, the 2 scenes differ only in the moving objects, which will therefore be located at a false distance. The delay theory is supported by several psychophysical [3,4,5,6,7] and electrophysiological investigations [8, 9]. Factors determining the size of the stereophenomenon include the density of the filter [3], the velocity of the pendulum [6], the level of illumination [3], and the distance between the observer and the pendulum [10].…”
Section: Introductionmentioning
confidence: 96%